1984
DOI: 10.2307/3899146
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Birds, Rodents, and Vegetation to Livestock Exclosure in a Semidesert Grassland Site

Abstract: Livestock have been excluded from a 3,160-ha range in southeastern Arizona since 1968. Compared to an adjacent continuously grazed area, in 1981-82 a protected upland site supported 45% more grass cover, a comparatively heterogeneous grass community, and 4 times as many shrubs. Grama grasses (Bouteloua spp.) were equally common in and outside the exclosure, while a variety of other species, especially plains lovegrass (Eragrostis intermedia) and Arizona cottontop (Trichachne cal~ornicum) were much more abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
3
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 4 publications
7
111
3
2
Order By: Relevance
“…These results are not consistent with several works that have demonstrated exclosures having positive effects on the growth of the vegetation (Morris and Jensen, 1998;Derner et al, 2006;Bock et al, 1984;Cheng et al, 2011). However, other studies have shown that exclosure is detrimental to the vegetation because of the lack of livestock grazing (McNaughton, 1983;Knapp and Seastedt, 1986).…”
Section: Effect Of Exclosure On Vegetation Structurecontrasting
confidence: 92%
See 2 more Smart Citations
“…These results are not consistent with several works that have demonstrated exclosures having positive effects on the growth of the vegetation (Morris and Jensen, 1998;Derner et al, 2006;Bock et al, 1984;Cheng et al, 2011). However, other studies have shown that exclosure is detrimental to the vegetation because of the lack of livestock grazing (McNaughton, 1983;Knapp and Seastedt, 1986).…”
Section: Effect Of Exclosure On Vegetation Structurecontrasting
confidence: 92%
“…Livestock exclosures have a potential value in assessing the effects of grazing upon vegetation and C sequestration in the grasslands (Bock et al, 1984;Cheng et al, 2011;He et al, 2011;Li et al, 2012;Su et al, 2003). Exclosures appear to favor higher community diversity and productivity compared with grazing in the arid grasslands (Bock et al, 1984;Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of eVect may largely be due to rotational grazing and low stocking rates within KLEE. Results from other studies indicate that cattle generally have an adverse eVect on bird diversity, with grazed areas supporting fewer bird species (Bock et al 1984;Gonnet 2001;Taylor 1986;Temple et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Cattle generally have negative eVects on bird diversity and abundance (Bock et al 1984;Taylor 1986;Temple et al 1999;Gonnet 2001;Soderstrom et al 2001; but see Knopf 1996). However, little research is devoted to understanding how large wild mammals inXuence birds, either directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%